Peningkatan Aktivitas dan Kemampuan Mengajar Melalui Pembinaan Konsepsi Model Up Grading Learning bagi Guru Kelas Sekolah Dasar - Sulastri Sulastri (Jurnal Pendidikan Dasar, 2021)
The purpose of this research is describing the 1 Waru Elementary School ClassTeachers’ ability in teaching on the First Semester and 2019/2020 Year Acedemic through thecoaching conception of Up Grading Learning model. This research is School Action Research(SAR). The action of this research is the coaching. This research takes on 2 cycles, which areFirst Cycle and Second Cycle. This research takes place on the 1 Waru Elementary School.Meanwhile this research takes time on the First Semester and 2019/2020 Year Academic. Thesubjects of this research are 6 persons. The technique of collecting data is using non testtechnique. The tool of collecting data is using the sheet of observation. The technique of dataanalyzing is using comparative descriptive. The result of this research is the 1 WaruElementary School Class Teachers’ ability in teaching increased through the coachingconception of Up Grading Learning model from Not Good category into Good category.